Fundamental of Entrepreneurship ENT300 : Smash Your Way / Mohd Hameez Ekhwan Kemis... [et al.] - Kemis, Mohd Hameez Ekhwan; Joan@Johan, Mohammad Izzuddin; Saharuddin, Sabuddin; Sutarman, Sunardi; Hadi, Muhammad Haziq (2016)
We choose this business because there is a huge potential in providing comfortable sport place for our target market. Even though there is an existing business that provides the badminton court renting service, we believe that we have competitive advantage on this business. From our observation, the existing badminton court rental in Samarahan district is not satisfying their customer besides it is far away from the educational institution.